Identification of Occult Parechymal Disease Such as Emphysema or Airway Disease Using Screening Computed Tomography - Tsushima, Kenji; Sone, Shusuke; Fujimoto, Keisaku; Kubo, Keishi; Morita, Satoshi; Takegami, Misa; Fukuhara, Shunichi (Chronic obstructive pulmonary disease, 2010)
ABSTRACT Rationale: Chronic obstructive pulmonary disease (COPD) is a major public health problem. This study was performed to determine whether the low attenuation area (LAA) and visual score provided by low-dose computed tomography (CT) can be used to detect occult parenchymal disease, such as insidious COPD. Methods: Each participant underwent low-dose CT scan and pulmonary function tests. The LAA% of the corresponding lung area was calculated. The cut-off level between the normal lung density area and LAA was defined as -960 HU, and the severity of emphysematous change (visual score) and LAA% were evaluated on three same chest CT slices obtained at full inspiration. Results: Forty-eight of 2,247 individuals including 1058 non-smokers and 1189 smokers were diagnosed with COPD. Chest CT findings in individuals diagnosed with COPD showed centrilobular emphysema (50%), however, 17 of the subjects diagnosed with COPD had normal screening CT findings. Thirty-one subjects diagnosed with COPD showed a positive visual score, and 27 individuals with COPD showed LAA% of more than 30. Nine of 17 subjects with a negative visual score showed LAA% of more than 30. The visual score in smokers was significantly higher than that of non-smokers. The lung function in smokers was lower than that of non-smokers. Smokers also showed higher frequencies of chest CT abnormalities. Conclusion: Low-dose CT scans detected LAA and a positive visual score before COPD associated with an impaired lung function develops. Smokers with normal spirometry had a potential to develop an airflow obstruction accompanied with abnormal CT findings.